Self-Reported, Work-Related Injuries and Illnesses Among Restaurant Workers in Shiraz City, South of Iran - Mehdi Jahangiri; Fahimeh Eskandari; Narges Karimi; Soheil Hasanipour; Mahnaz Shakerian; Asma Zare (Ubiquity Press, 2019)
Background: Restaurant sector is one of the most rapidly developing sectors in the world and there is evidence that restaurant industry has high levels of work-related diseases and injuries. This study examined the prevalence of self-reported work-related injuries and illness (WRIIs) and their association with demographic variables among restaurant workers in Shiraz, the capital of Fars Province, Iran. Methods: In this cross-sectional study, 300 randomly selected restaurant workers completed a self-statement, research-made questionnaire regarding the prevalence of self-reported WRIIs, in Shiraz, Iran. Statistical analyses were performed using SPSS version 20. Results: A high prevalence of work-related injuries (84%) and musculoskeletal disorders (70%) was reported among restaurant workers. Cuts and lacerations, arising from accidents with knives, were the most common injuries seen, followed by burns, falls, slips and trips. Moreover, the prevalence of occupational accidents had a significant association with work experience (p = 0.012), cooking (p < 0.001), as well as preparation and washing (p = 0.011). Age (p < 0.001) and work experience (p < 0.001) had a significance association with the prevalence of musculoskeletal disorders. Conclusion: Preventive measures and polices, through providing occupational health and safety services including trainings, personal protective equipment and health examinations, should be taken as to restaurants and catering industry in Iran.